(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2025)
This research is motivated by a growing phenomenon in Setiris Village, namely mutual assistance (ta’awun), which ideally should be practiced sincerely without expecting anything in return. However, over time, many villagers have come to perceive ta’awun as serving personal benefit rather than collective solidarity. The primary purpose of this practice is to assist families in organizing major village events that require substantial financial resources. This mindset has created disparities, where families from middle- to upper-class backgrounds tend to receive significantly more financial support than those from lower socioeconomic backgrounds. This study employs field research with a qualitative approach, focusing on written sources, particularly Hadith of Sunan al-Tirmidhi No. 1425. The findings reveal that the principle of ta’awun must be implemented in line with the spirit of the hadith, since all actions should be grounded in Islamic law. The practice of pekatan sekampung (village collective gathering), which also applies the principle of ta’awun, is guided by the hadith on mutual assistance. Keywords: Hadith, Ta’awun, Pekat Sekampung